Ecology and life cycle of a Nitella sp. from Capel Wetlands, Western Australia - Annan, Isaac; John, Jacob (Royal Society of Western Australia, 2012)
The morphology, ecology, life cycle pattern and taxonomy of a Nitella sp., a charophyte from three sand-mine-void lakes at the Capel Wetlands Centre, were investigated both in the field and in the laboratory. Water depth was positively correlated with the height of the Nitella sp. Low numbers of gametangia were associated with high water depth. Life cycle of the charophyte was shown to be adapted to the hydrological regime and water quality of the temporary lakes at Capel Wetlands within the pH range of 5 to 9. Laboratory cultures of the species as well as its occurrence in lakes in the Perth Metropolitan region under various trophic conditions indicate that the species has wide ecological tolerance. The charophyte begins its life cycle with autumn rains filling the temporary wetlands and continues to grow throughout the winter. By spring, reproduction is initiated. Mature oospores are produced by the end of summer, coinciding with the decline in water level followed by the drying of the lakes. Morphology of vegetative and reproductive structures, reproductive state and ultrastructure of oospores were combined to provide a description of the species. The number of accessory branchlets was found to be variable. The Nitella species is placed under the subgenus Decandollea section Decandollea and shares characters of N. congesta (R Brown) A Braun and N. lhotzkyi A Braun.